Basic of information tehcnology for librarians and information scientists - Dhiman, Anil Kumar (Ess Ess Publications, 2003)
Contents of material: Introduction. Computer basics. Harware-Computer. Software-Computer. Data communication and networking. Internet: Basics and tools.